PENGARUH PSIKOEDUKASI TERHADAP SELFEFFICACY DAN MOTIVASI MENJALANI PENGOBATAN PADA PASIEN KANKER PAYUDARA - Yora Nopriani; Fira Mitha Rustika (Jurnal Kesehatan dan Pembangunan, 2026)
Diabetes Mellitus (DM) is a chronic disease with increasing prevalence and can lead to various complications if not properly managed, including through adherence to dietary patterns. However, many patients still lack adequate knowledge about diabetes diets and tend to be non-compliant with recommendations from healthcare professionals. Therefore, an easy-to-understand, engaging, and self-study education format, such as a booklet, is needed. This study aimed to determine the effect of booklet-based education on the knowledge and dietary compliance of diabetes mellitus patients at the Bina Sejahtera Bukit Sangkal Elderly Health Post using a pre-experimental, one-group pre-test, post-test design. The study sample consisted of 30 respondents selected through purposive sampling. Data were collected using questionnaires before and after the booklet-based education, and then analyzed using the Wilcoxon test. The results showed a significant increase in respondents' knowledge and dietary adherence after receiving education using booklets, with a p-value of 0.000 (p < 0.05). Based on these results, it can be concluded that health education using booklets is effective in improving knowledge and dietary adherence in patients with diabetes mellitus. Therefore, this medium is suitable for use as an alternative education tool in healthcare settings, particularly for elderly patients.